PERTAUTAN ANTARA ASPEK INTELEKTUAL DAN MISTIS DALAM NOVEL LANANG KARYA YONATHAN RAHARDJO - Sugiarti Sugiarti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the connection between the intellectual and mystical aspectsin Lanang, a novel by Yonathan Rahardjo. It employed the qualitative phenomenologicalapproach using principles in qualitative content analysis to understand text messagesdescriptively. The data sources were Lanang and the results of interviews with theauthor. The data comprised the story sequence relevant to the research objectives andimportant information obtained from literature review. The findings are as follows. First,the intellectual aspect stimulates awareness that the technology sophistication is capableof changing what is impossible into what is possible, such as animal biotechnologyengineering. Second, the mystical aspect originates from beliefs in a local tradition thatmay be illogical and full of weirdness but people still believe them.